Follicular thyroid carcinoma presenting with pathological fracture of the humerus at initial diagnosis. Issue 1 (20th January 2017) - Yang, Wanding; Cho, WaiSum; Das, Sudip; Conboy, Peter
Abstract: Differentiated carcinomas of the thyroid gland usually have a good prognosis with prognosis often discussed in terms of 20 year survival. Nevertheless its 10-year-survival rate decreases when accompanied by distant metastasis. Follicular thyroid cancer (FTC) is the second most common thyroid cancer and usually presents with a solitary thyroid nodule with or without cervical lymphadenopathy. Distance metastasis at initial diagnosis is seldom observed with incidence range from 1 to 9%. In cases of bone metastasis, the incidence is only 2–3% and weight-bearing skeleton is preferentially affected. In our case, we present a patient with FTC that metastasized to the upper limb causing severe pain and pathological fracture at the initial presentation.